In China's Shadow : Regional Perspectives on Chinese Foreign Policy and Military Development - Pollack, Jonathan D.; Yang, Richard H. (RAND, 1998)
The papers in this collection were first presented at a conference on "Chinese Security Policy and the Future of Asia." The authors, each representing different countries and regions affected by the growth of Chinese power, were asked to address four major questions: (1) China's position in the present and future security environment of the given country or region; (2) principal sources of tension between China and the particular country or region; (3) prevailing opinion in the country or region toward China's efforts at military modernization; and (4) the principal political, security, and economic strategies for responding to China's emergent power and military role. The purpose was to reveal elements of commonality and difference in national strategies.
" ... revised versions of papers originally prepared for a conference on 'Chinese Security Policy and the Future of Asia, ' held in Honolulu, Hawaii between June 26-28, 1996 ... undertaken jointly by the Chinese Council for Advanced Policy Studies ... and the RAND Center for Asia-Pacific Policy ..."--Preface.
"National Security Research Division."
"CF-137-CAPP"--Page 4 of cover.
Keywords: China -- Military relations -- Asia -- Congresses.; Asia -- Military relations -- China -- Congresses.; Asie -- Relations militaires -- Chine -- Congrès.; TECHNOLOGY & ENGINEERING -- Military Science.; HISTORY -- Military -- Other.; Military relations; Asia; China; Außenpolitik; Kongress; Militärpolitik; Conference papers and proceedings